4.1.2 Problems 101 to 200

Table 4.3: Problems not solved by Mathematica

#

ODE

Mathematica

Maple

5127

\[ {}\left (a +\left (x +y\right ) x \right ) y^{\prime } = b \left (x +y\right ) y \]

5187

\[ {}\left (\operatorname {g0} \left (x \right )+y \operatorname {g1} \left (x \right )\right ) y^{\prime } = \operatorname {f0} \left (x \right )+\operatorname {f1} \left (x \right ) y+\operatorname {f2} \left (x \right ) y^{2}+\operatorname {f3} \left (x \right ) y^{3} \]

5355

\[ {}{y^{\prime }}^{2} = f \left (x \right )^{2} \left (y-u \left (x \right )\right )^{2} \left (y-a \right ) \left (y-b \right ) \]

5490

\[ {}x^{2} {y^{\prime }}^{2}+x \left (x^{2}+x y-2 y\right ) y^{\prime }+\left (1-x \right ) \left (x^{2}-y\right ) y = 0 \]

5560

\[ {}\left (a^{2}-2 a x y+y^{2}\right ) {y^{\prime }}^{2}+2 a y y^{\prime }+y^{2} = 0 \]

5595

\[ {}{y^{\prime }}^{3}-x y^{\prime }+a y = 0 \]

5596

\[ {}{y^{\prime }}^{3}+2 x y^{\prime }-y = 0 \]

5597

\[ {}{y^{\prime }}^{3}-2 x y^{\prime }-y = 0 \]

5604

\[ {}{y^{\prime }}^{3}+{\mathrm e}^{3 x -2 y} \left (y^{\prime }-1\right ) = 0 \]

5605

\[ {}{y^{\prime }}^{3}+{\mathrm e}^{-2 y} \left ({\mathrm e}^{2 x}+{\mathrm e}^{3 x}\right ) y^{\prime }-{\mathrm e}^{3 x -2 y} = 0 \]

5610

\[ {}{y^{\prime }}^{3}+\operatorname {a0} {y^{\prime }}^{2}+\operatorname {a1} y^{\prime }+\operatorname {a2} +\operatorname {a3} y = 0 \]

5618

\[ {}2 {y^{\prime }}^{3}+x y^{\prime }-2 y = 0 \]

5619

\[ {}2 {y^{\prime }}^{3}+{y^{\prime }}^{2}-y = 0 \]

5622

\[ {}8 {y^{\prime }}^{3}+12 {y^{\prime }}^{2} = 27 x +27 y \]

5631

\[ {}x {y^{\prime }}^{3}-3 y {y^{\prime }}^{2} x^{2}+x \left (x^{5}+3 y^{2}\right ) y^{\prime }-2 x^{5} y-y^{3} = 0 \]

5634

\[ {}x^{6} {y^{\prime }}^{3}-x y^{\prime }-y = 0 \]

5638

\[ {}y^{2} {y^{\prime }}^{3}-x y^{\prime }+y = 0 \]

5643

\[ {}y^{3} {y^{\prime }}^{3}-\left (1-3 x \right ) y^{2} {y^{\prime }}^{2}+3 x^{2} y y^{\prime }+x^{3}-y^{2} = 0 \]

5649

\[ {}{y^{\prime }}^{4}+x y^{\prime }-3 y = 0 \]

5659

\[ {}x^{2} \left ({y^{\prime }}^{6}+3 y^{4}+3 y^{2}+1\right ) = a^{2} \]

5730

\[ {}\frac {x^{n} y^{\prime }}{b y^{2}-c \,x^{2 a}}-\frac {a y x^{a -1}}{b y^{2}-c \,x^{2 a}}+x^{a -1} = 0 \]

5795

\[ {}x +y+\left (3 x +3 y-4\right ) y^{\prime } = 0 \]

6012

\[ {}y^{\prime \prime } = 2 y y^{\prime } \]

6183

\[ {}y^{\prime \prime }+y y^{\prime } = 0 \]

6184

\[ {}y^{\prime \prime }+y y^{\prime } = 0 \]

6185

\[ {}y^{\prime \prime }+y y^{\prime } = 0 \]

6261

\[ {}s^{2}+s^{\prime } = \frac {s+1}{s t} \]

6295

\[ {}x^{\prime }+t x = {\mathrm e}^{x} \]

6298

\[ {}x x^{\prime }+t^{2} x = \sin \left (t \right ) \]

6689

\[ {}{y^{\prime }}^{3}-4 x^{4} y^{\prime }+8 x^{3} y = 0 \]

6877

\[ {}x y^{\prime \prime \prime }-{y^{\prime }}^{4}+y = 0 \]

6879

\[ {}u^{\prime \prime }+u^{\prime }+u = \cos \left (r +u\right ) \]

6882

\[ {}x^{\prime \prime }-\left (1-\frac {{x^{\prime }}^{2}}{3}\right ) x^{\prime }+x = 0 \]

6884

\[ {}\sin \left (x^{\prime }\right )+y^{3} x = \sin \left (y \right ) \]

6971

\[ {}y^{\prime \prime }+4 y = 0 \]

6976

\[ {}y^{\prime \prime }+4 y = 0 \]

6979

\[ {}2 y^{\prime \prime }-3 y^{2} = 0 \]

6995

\[ {}y^{\prime } = 6 \sqrt {y}+5 x^{3} \]

7018

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7019

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7020

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7021

\[ {}y^{\prime } = {\mathrm e}^{-\frac {x y^{2}}{100}} \]

7129

\[ {}y^{\prime } = \sqrt {1+y^{2}}\, \sin \left (y\right )^{2} \]

7138

\[ {}y^{\prime } = -\frac {5+8 x}{3 y^{2}+1} \]

7139

\[ {}y^{\prime } = -\frac {5+8 x}{3 y^{2}+1} \]

7140

\[ {}y^{\prime } = -\frac {5+8 x}{3 y^{2}+1} \]

7141

\[ {}y^{\prime } = -\frac {5+8 x}{3 y^{2}+1} \]

7196

\[ {}x y^{\prime }-4 y = x^{6} {\mathrm e}^{x} \]

7429

\[ {}x^{2}+2 x y-y^{2}+\left (y^{2}+2 x y-x^{2}\right ) y^{\prime } = 0 \]

7481

\[ {}y^{\prime \prime }-\cot \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0 \]

7485

\[ {}y^{\prime \prime \prime }-2 x y^{\prime \prime }+4 x^{2} y^{\prime }+8 x^{3} y = 0 \]

7486

\[ {}y^{\prime \prime }+x \left (1-x \right ) y^{\prime }+y \,{\mathrm e}^{x} = 0 \]

7768

\[ {}y^{\prime \prime }+\sin \left (y\right ) = 0 \]

7772

\[ {}[y_{1}^{\prime }\left (x \right ) = 3 y_{1} \left (x \right )+x y_{3} \left (x \right ), y_{2}^{\prime }\left (x \right ) = y_{2} \left (x \right )+x^{3} y_{3} \left (x \right ), y_{3}^{\prime }\left (x \right ) = 2 x y_{1} \left (x \right )-y_{2} \left (x \right )+{\mathrm e}^{x} y_{3} \left (x \right )] \]

7837

\[ {}x \ln \left (x \right ) y^{\prime }+y = 3 x^{3} \]

7853

\[ {}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime } \]

7914

\[ {}y^{\prime \prime } = y^{\prime } {\mathrm e}^{y} \]

8210

\[ {}[x^{\prime }\left (t \right ) = x \left (t \right ) y \left (t \right )+1, y^{\prime }\left (t \right ) = -x \left (t \right )+y \left (t \right )] \]

8211

\[ {}[x^{\prime }\left (t \right ) = t y \left (t \right )+1, y^{\prime }\left (t \right ) = -t x \left (t \right )+y \left (t \right )] \]

8217

\[ {}y^{\prime } = y+x \,{\mathrm e}^{y} \]

8249

\[ {}y^{\prime \prime }+5 x y^{\prime }+\sqrt {x}\, y = 0 \]

8475

\[ {}y = x^{6} {y^{\prime }}^{3}-x y^{\prime } \]

8479

\[ {}2 {y^{\prime }}^{3}+x y^{\prime }-2 y = 0 \]

8481

\[ {}{y^{\prime }}^{3}+2 x y^{\prime }-y = 0 \]

8507

\[ {}2 y^{\prime \prime } = \sin \left (2 y\right ) \]

8508

\[ {}2 y^{\prime \prime } = \sin \left (2 y\right ) \]

8524

\[ {}{y^{\prime \prime }}^{2}-2 y^{\prime \prime }+{y^{\prime }}^{2}-2 x y^{\prime }+x^{2} = 0 \]

8526

\[ {}{y^{\prime \prime }}^{3} = 12 y^{\prime } \left (x y^{\prime \prime }-2 y^{\prime }\right ) \]

8542

\[ {}{y^{\prime }}^{4}+x y^{\prime }-3 y = 0 \]

8546

\[ {}{y^{\prime }}^{3}-2 x y^{\prime }-y = 0 \]

8731

\[ {}y^{\prime } = \sqrt {-y^{2}-x^{2}+1} \]

8770

\[ {}y^{\prime } = -4 \sin \left (x -y\right )-4 \]

8775

\[ {}y y^{\prime \prime } = x \]

8776

\[ {}y^{2} y^{\prime \prime } = x \]

8778

\[ {}3 y y^{\prime \prime } = \sin \left (x \right ) \]

8846

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0 \]

8847

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0 \]

8850

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0 \]

8851

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0 \]

8855

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0 \]

8857

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0 \]

8880

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+{y^{\prime }}^{2} = x \]

8882

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0 \]

8921

\[ {}{y^{\prime }}^{2}+y^{2} = \sec \left (x \right )^{4} \]

8956

\[ {}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0 \]

8984

\[ {}y^{\prime } = \frac {x y+3 x -2 y+6}{x y-3 x -2 y+6} \]

9013

\[ {}y^{\prime } = \cos \left (x \right )+\frac {y^{2}}{x} \]

9058

\[ {}t y^{\prime }+y = t \]

9061

\[ {}t y^{\prime }+y = 0 \]

9093

\[ {}{y^{\prime \prime }}^{2}+y^{\prime }+y = 0 \]

9144

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 4 \cos \left (\ln \left (1+x \right )\right ) \]

9236

\[ {}\left (2 x^{5}+1\right ) y^{\prime \prime }+14 x^{4} y^{\prime }+10 x^{3} y = 0 \]

9238

\[ {}\left (x^{8}+1\right ) y^{\prime \prime }-16 x^{7} y^{\prime }+72 x^{6} y = 0 \]

9656

\[ {}\left (2 x^{5}+1\right ) y^{\prime \prime }+14 x^{4} y^{\prime }+10 x^{3} y = 0 \]

9658

\[ {}\left (x^{8}+1\right ) y^{\prime \prime }-16 x^{7} y^{\prime }+72 x^{6} y = 0 \]

10061

\[ {}y^{\prime }-a \left (x^{n}-x \right ) y^{3}-y^{2} = 0 \]

10062

\[ {}y^{\prime }-\left (a \,x^{n}+b x \right ) y^{3}-c y^{2} = 0 \]

10063

\[ {}y^{\prime }+a \phi ^{\prime }\left (x \right ) y^{3}+6 a \phi \left (x \right ) y^{2}+\frac {\left (2 a +1\right ) y \phi ^{\prime \prime }\left (x \right )}{\phi ^{\prime }\left (x \right )}+2 a +2 = 0 \]

10064

\[ {}y^{\prime }-f_{3} \left (x \right ) y^{3}-f_{2} \left (x \right ) y^{2}-f_{1} \left (x \right ) y-f_{0} \left (x \right ) = 0 \]

10069

\[ {}y^{\prime }-f \left (x \right ) y^{n}-g \left (x \right ) y-h \left (x \right ) = 0 \]